2021
DOI: 10.3390/sym13122358
|View full text |Cite
|
Sign up to set email alerts
|

Entropy Analysis for Cilia-Generated Motion of Cu-Blood Flow of Nanofluid in an Annulus

Abstract: In this study, a novel model of entropy generation effects measured in the Cu-blood flow of a nanofluid under the effect of ciliary-oriented motion is proposed. The effects of viscous dissipation are also taken into account. The physical model was composed with the incorporation of a low Reynolds number and long-wavelength phenomena. The exact solutions for the axial velocity, temperature and pressure gradient distribution were achieved successfully. Key findings are presented through a strategy of plotting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…As heat transport occurs due to temperature differences, the three primary mechanisms of heat transfer are conduction, convection, and radiation. Improving heat transport is important in a ciliated movement [15][16][17][18][19]. Akbar and Butt [20] investigated the viscoelastic fluid model under the impact of heat transfer to better understand the role of cilia in the respiratory system and its essential roles associated with fluid transport in the human body.…”
Section: Introductionmentioning
confidence: 99%
“…As heat transport occurs due to temperature differences, the three primary mechanisms of heat transfer are conduction, convection, and radiation. Improving heat transport is important in a ciliated movement [15][16][17][18][19]. Akbar and Butt [20] investigated the viscoelastic fluid model under the impact of heat transfer to better understand the role of cilia in the respiratory system and its essential roles associated with fluid transport in the human body.…”
Section: Introductionmentioning
confidence: 99%
“…An MHD biomimetic blood pump model was suggested by Ramesh et al [17]. Ashraf et al [18] and Riaz et al [19] claimed that epic cilia length enhances fluid flow rate in cilia-assisted motion of viscous fluid and water-based nanofluid in symmetric shaped conduit.…”
Section: Introductionmentioning
confidence: 99%
“…Some interesting studies of fabricated cilia in the perception of microfluidic processing, instantaneous mixing and pumping are mentioned [16][17][18][19]. In this regime, Javid et al [20] presented a mathematical model of pumping transport induced by cilia stimulated asymmetric metachronal waves and reported that prolonged cilia contribute to fluid flow enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Nagaraj et al (2018) introduced combined influence of magnetic and electric fields on synovial fluid in a biological bearing. Moreover, the topic of studying the nanofluid has played a vital role in explaining many physical phenomena as presented by Othman et al (2019), Moghaddaszadeh et al (2019), Bagherzadeh et al (2020), Zhang et al (2020), Riaz et al (2021a, 2021b) and Abo-Elkhair et al (2021).…”
Section: Introductionmentioning
confidence: 99%